Wage Equalization and Regional Misallocation: Evidence from Italian and German Provinces - Tito Boeri; Andrea Ichino; Enrico Moretti; Johanna Posch (Institute of Labor Economics (IZA), 2019)
In many European countries, wages are determined by collective bargaining agreements intended to improve wages and reduce inequality. We study the local and aggregate effects of collective bargaining in Italy and Germany. The two countries have similar geographical differences in firm productivity – with the North more productive than the South in Italy and the West more productive than the East in Germany – but have adopted different models of wage bargaining. Italy sets wages based on nationwide contracts that allow for limited local wage adjustments, while Germany has moved toward a more flexible system that allows for local bargaining. We find that, as a consequence, Italy exhibits limited geographical wage differences in nominal terms and almost no relationship between local productivity and local nominal wages, while Germany has larger geographic wage differences and a tighter link between local wages and local productivity. While the Italian system is successful at reducing nominal wage inequality, it also creates costly geographic imbalances. In Italy, low productivity provinces have significantly higher non-employment rates than high productivity provinces, because employers cannot lower wages, while in Germany the relationship between non-employment and productivity is significantly weaker. In Italy, the relationship between real wages and productivity is negative, with lower real wages in the North compared to the South, since the latter has low housing costs but similar nominal wages. Thus, conditional on having a job, Italian workers have higher purchasing power in the South, but the probability of having a job is higher in the North. We conclude that the Italian system has significant costs in terms of forgone aggregate earnings and employment because it generates a spatial equilibrium where workers queue for jobs in the South and remain unemployed while waiting. If Italy adopted the German system, aggregate employment and earnings would increase by 11.04% and 7.45%, respectively. Our findings are relevant for several other European countries with systems similar to Italy's.
Keywords: J20; 330; local labor markets